The Role of Modified Expansion Sphincter Pharyngoplasty in Multilevel Obstructive Sleep Apnea Syndrome Surgery - Lorusso,Francesco (2018)
Abstract Introduction Obstructive sleep apnea syndrome (OSAS) is a sleep disorder caused by an excessive narrowing of the pharyngeal airway that also collapses during inspiration, with an important role played by the lateral pharyngeal wall in the development of the obstruction. Objective To describe our surgical experience with modified expansion sphincter pharyngoplasty (MESP) in the management of lateral collapse in upper airway multilevel surgery. Methods A total of 20 patients with moderate to severe OSAS were recruited in the Ear, Nose and Throat (ENT) Department of the University of Palermo, Italy. All of the enrolled patients refused the ventilatory therapy. The subjects were evaluated for snoring, and daytime sleepiness had a clinical evaluation including collection of anthropometric data and ENT examination and rhinofibroscopy with Müller maneuver. The patients undergoing upper airway multilevel surgery and we selected for MESP the patients with an oropharyngeal transverse pattern of collapse at Müller maneuver. Results In the postoperative assessment, all of the patients reported a reduction in snoring scores and daytime sleepiness. We observed a reduction in the mean apnea-hypopnea index (AHI) of 57.5% of the sample, which decreased from a mean value of 41.7 ( ± 21.5) to 17.4 ( ± 8.9) (p< 0.05), with a success rate, according to the Sher criteria, of 65%. We observed very few postoperative complications. Conclusion Modified expansion sphincter pharyngoplasty in multilevel surgical therapy preceded by a careful selection of patients has proven to be effective in treating patients with moderate to severe syndromes.